2016
DOI: 10.1515/anre-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as a screening measure of overweight/obesity among Indian adults

Abstract: Neck circumference (NC) is an anthropometric measurement of differentiating body fat distributions and a marker of upper subcutaneous adiposity. The present study highlights the association and importance of NC as a suitable proxy screening measure of overweight/obesity as compared to the conventional anthropometric variables used among Indian adults. The present community based cross-sectional study was undertaken among 1169 Karbi adults (males: 625; females: 544) residing in Karbi Anglong district of Assam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 55 publications
(109 reference statements)
1
5
0
Order By: Relevance
“…In the present study, an attempt has been made to identify the reliability and acceptability of NC as a valid parameter over the conventionally used anthropometric measures (e.g., BMI and WC) for adiposity assessment and to estimate the sex-specific cut-offs among adult Asian Indian population. Studies have suggested the use of NC in combination with anthropometric measures separates the effects of visceral and subcutaneous body fat-mass and excess adiposity distributions [5,8,10,12,15,20]. Results of the present study have indicated positive associations of NC with BMI and WC in both sexes (p<0.01).…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…In the present study, an attempt has been made to identify the reliability and acceptability of NC as a valid parameter over the conventionally used anthropometric measures (e.g., BMI and WC) for adiposity assessment and to estimate the sex-specific cut-offs among adult Asian Indian population. Studies have suggested the use of NC in combination with anthropometric measures separates the effects of visceral and subcutaneous body fat-mass and excess adiposity distributions [5,8,10,12,15,20]. Results of the present study have indicated positive associations of NC with BMI and WC in both sexes (p<0.01).…”
Section: Discussionsupporting
confidence: 51%
“…Results of the present study have indicated positive associations of NC with BMI and WC in both sexes (p<0.01). Several researchers have reported similar significant associations of NC with BMI and WC [2,3,4,5,8,20]. Results of the linear regression analysis showed that NC was the best predictor variables of BMI than WC (Figure 1).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations